Mengoptimalkan Pencegahan Serangan Brute Force pada Linux melalui Penerapan Metode Aplikasi IDS Snort - Dody Hidayat; Ramli Ramli (JITEKH, 2023)
Network security system on the server is an important factor to ensure the stability, integrity and validity of data. Implementation of Snort-based Intrusion Detection System can save software procurement costs because it is free and reliable enough to detect security attacks. Snort-based IDS system can be implemented on Linux operating system. An attack may or may not be detected by Snort IDS depending on the presence or absence of appropriate rules. The testing process used is a port scanning attack technique, brute force attack technique, and hacker IP address blocking. The port scanning attack technique can generate important information about a network and can detect open ports, including port 22, which is the secure shell. The brute force attack technique can generate illegal username and password combinations on the server system. IDS snort can detect incoming attacks on the server system, then IDS snort can detect the IP address that is trying to hack the server system. Ensure data on the server system is secure by allowing the administrator to track any hacker activity.